Applied reliability - Tobias, Paul A. (CRC/Taylor & Francis, 2012)
"This popular book is an easy-to-use guide that addresses basic descriptive statistics, reliability concepts, the exponential distribution, the Weibull distribution, the lognormal distribution, reliability data plotting, acceleration models, life test data analysis and systems models, and much more. The third edition includes a new chapter on Bayesian reliability analysis and expanded, updated coverage of repairable system modeling. Taking a practical and example-oriented approach to reliability analysis, it also provides detailed illustrations of software implementation throughout using several widely available software packages. Software and other files are available for download at www.crcpress.com"--